Brain activation in older adults with hypertension and normotension during standing balance task: an fNIRS study - Fan, Weichao; Zeng, Qing; Zheng, Peng; Wen, Shuyang; Li, Gege; Fan, Tao; Huang, Guozhi; Zheng, Manxu; Luo, Qinglu (Frontiers in Aging Neuroscience, 2024)
Background Hypertension (HT) is a common chronic disease in older adults. It not only leads to dizziness and other symptoms affecting balance in older adults with HT but also affects the hemodynamics of the cerebral cortex. At present, potential neural mechanisms of balance control in older adults with HT are still unclear. Therefore, this study aimed to explore the differences in the center of pressure (COP) and cerebral cortex activation between older adults with HT and normotension (NT) during standing balance tasks. This study May provide guidance for the early detection of the risk of falls among older adults with HT and the development of clinical rehabilitation strategies. Methods In this cross-sectional study, 30 older adults with NT (NT group) and 27 older adults with HT (HT group) were subjected to three conditions: task 1, standing with eyes open on a stable surface; task 2, standing with eyes closed on a stable surface; and task 3, standing with eyes open on the surface of the foam pad. Cortical hemodynamic reactions were measured using functional near-infrared spectroscopy, and COP parameters were measured using a force plate. Results The mean velocity of the COP in the medial–lateral direction in the NT group was significantly higher than that in the HT group (F = 5.955, p = 0.018) during task 3. When proprioception was disturbed, the activation of the left premotor cortex and supplementary motor cortex in the HT group was significantly lower than that in the NT group (F = 14.381, p < 0.001). Conclusion The standing balance function of older adults with HT does not appear to be worse based on COP parameters than those of older adults with NT. This study revealed that the changes in the central cortex related to standing balance appear to be more indicative of balance control deficits in older adults with HT than changes in peripheral COP parameters, suggesting the importance of the early evaluation of cortical activation in older adults with HT at risk of falls.